Root Cause Analysis Ofof Some Reported Radiological Events - Bakr, Wafaa F. (International Journal of Scientific Research and Management (IJSRM), 2017)
Lessons learned from past events are a way for improving the national infrastructure related to safety regulation and emergency preparedness. Root cause analysis is a tool required to identify factors that lead to the occurrence of the events and to develop the effective strategies to avoid the recurrence of such events. The aim of this work is to investigate the root cause analysis for most reoccurred international reported radiological events. The study covered 26 reported overexposure events in industrial radiography during the period from 2012 to 2016. The results of the analysis showed that the most common and repeated cause of overexposure to the workers in industrial radiography is related to human error. More investigations were focused on this type of error in this study. The concluded investigations help the regulatory bodies and licensee for enhancing and improving their radiological regime in industrial radiography field.